Infection After Hysterectomy - David L. Hemsell (Hindawi Limited, 1997)
Antibiotic prophylaxis and advances in technology have reduced operative site infections after hysterectomy to a minimum. Pelvic infections are the most common infection type and respond promptly to a variety of parenteral single-agent and combination antibiotic regimens. Oral antibiotic regimens following parenteral therapy are unnecessary. Abdominal incision infections are less common than pelvic infections, less common than seromas or hematomas, and usually do not require antimicrobial therapy. Abscesses or infected hematomas require parenteral antimicrobial therapy, and drainage of those located above the cuff will predictably shorten therapy time. With early discharge from the hospital, many infections will not become evident until after the patient is home. For that reason, it is important that the patient's discharge instructions outline symptoms and signs associated with these infections so she can present for care at the earliest possible time.